2023
DOI: 10.3390/app13106023
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Protocols for Determining the Non-Reactive Agility of Female Basketball Players Based on Familiarization and Validity Tests

Abstract: The aim of this study was to implement a familiarization protocol and to determine the constructive validity of four different non-reactive agility tests on a sample of professional female basketball players (n = 12; age: 18.17 ± 1.90 years). Following the protocol, the participants performed standardized tests three times (the Agility t-test and the Sprint 9-3-6-3-9 m with 180° Turns), while the lateral agility, universal agility, frontal agility, and semicircular agility tests were repeated five times each, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Thus, the players were able to respond more efficiently to stimuli and perform complex movements with improved precision and coordination under conditions specific to basketball training. The results of our study are confirmed by previous studies [ 2 , 3 , 4 ], which have examined how the implementation of Fitlight technologies in training methodology contributes to the improvement of athletic performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the players were able to respond more efficiently to stimuli and perform complex movements with improved precision and coordination under conditions specific to basketball training. The results of our study are confirmed by previous studies [ 2 , 3 , 4 ], which have examined how the implementation of Fitlight technologies in training methodology contributes to the improvement of athletic performance.…”
Section: Discussionsupporting
confidence: 89%
“…Sports performance is influenced by the input of specialized informational technology for monitoring the training and condition of athletes. Fitlight is a digital technology adapted to the training and evaluation process in sports, which relies on light simulation and consists of a system of wireless lights (spots) that can light up randomly or be controlled by setting the dedicated software [ 1 , 2 , 3 , 4 ]. Fitlight has great applicability in developing RT and coordination due to the various settings and versatility of the arrangement of the luminous spots according to the specific training and sport practiced [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While our study offers a broad analysis of the Fitlight system across various age groups in basketball, Hadzovic [49] zooms in on a specific segment of athletes, highlighting a targeted approach in agility training for professional female basketball players. It introduces innovative protocols for evaluating non-reactive agility, a component crucial in basketball but often less highlighted; in contrast, our contribution lies in our comparative analysis of traditional and modern training methods across various age groups, offering a broader perspective on agility training efficacy in youth basketball.…”
Section: Discussionmentioning
confidence: 99%
“…Our comprehensive analysis across multiple studies reveals a significant trend towards the integration of advanced technology, like the Fitlight Training System, in sports training, particularly for youth basketball. While studies like Hassan's [8] focus on specific skill enhancements and Hadzovic's [49] on professional female athletes, our research broadens the spectrum by comparing traditional and modern methods across various age groups. This holistic approach, enriched by theoretical insights from Bekris [50] and cognitive perspectives from Silvestri [51], underscores the multifaceted benefits of such training.…”
Section: Discussionmentioning
confidence: 99%
“…For talented young basketball players (national teams), power outputs in jumps and accelerations are an important selection indicator for both sexes (Arede et al, 2019). The use of tests for coordination (determining lateral and semicircular agility) in women's youth basketball is supported by (Hadžović et al, 2023).…”
Section: Introductionmentioning
confidence: 99%